Superalloys 2012 : proceedings of the 12th international symposium on superalloys, held September 9-13, 2012 at Seven Springs Mountain Resort, Seven Springs, PA - Huron, Eric S. (Wiley, 2012)
A superalloy, or high-performance alloy, is an alloy that exhibits excellent mechanical strength at high temperatures. Superalloy development has been driven primarily by the aerospace and power industries. This compilation of papers from the Twelfth International Symposium on Superalloys, held from September 9-13, 2012, offers the most recent technical information on this class of materials. It covers all aspects of the development, production, behavior and integration of superalloys, and related high temperature materials, into gas turbines for aircraft, power generation and other applications as well as cast, wrought and powder superalloys, and associated coating systems.